2014
DOI: 10.1177/0267323114545709
|View full text |Cite
|
Sign up to set email alerts
|

Populist rhetoric in politics and media: A longitudinal study of the Netherlands

Abstract: Many claim that populism in the Netherlands has grown over the last 10 years; that it spreads among mainstream parties; that its success has to do with the media, who pay more and more attention to populist parties and immigration issues; but that it is difficult to distinguish between political populism intended for the media and populism by the media. In a longitudinal content analysis of newspapers, television news, talk shows and party political broadcasts, covering seven elections in nearly 20 years, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 18 publications
1
75
1
6
Order By: Relevance
“…A set of literature, however, has addressed this issue in several countries in Europe where populist parties have gained some terrain, such as Italy (Lanzane and Woods, 2015), Finland (Herkman, 2017), France (Mondon, 2014;Nilsson, 2015;Williams, 2011), the Netherlands (Bos and Brants, 2014;Pas et al, 2011;Hameleers and Schmuck, 2017), the UK (Cushion et al, 2015;Deacon and Wring, 2016;Reed, 2016), or Sweden (Nilsson and Carlsson, 2014).…”
Section: The Limits Of Party Offermentioning
confidence: 99%
“…A set of literature, however, has addressed this issue in several countries in Europe where populist parties have gained some terrain, such as Italy (Lanzane and Woods, 2015), Finland (Herkman, 2017), France (Mondon, 2014;Nilsson, 2015;Williams, 2011), the Netherlands (Bos and Brants, 2014;Pas et al, 2011;Hameleers and Schmuck, 2017), the UK (Cushion et al, 2015;Deacon and Wring, 2016;Reed, 2016), or Sweden (Nilsson and Carlsson, 2014).…”
Section: The Limits Of Party Offermentioning
confidence: 99%
“…Bos and Brants (2014) claim that media populism is a consequence of the news-values of an increasingly 'market-driven journalism' (p. 707), which may be transversal to the media, both 'old' and 'new'. Alternatively, these authors claim that media populism can also be a result of the attitudes of journalists who work in tabloid-like, infotainment genres, proudly taking distance from the status quo -unlike those in the elite media -and thus more prone to publicly voicing 'antiparty, anti-establishment, anti-corruption and anti-immigration sentiments' (Bos and Brants, 2014: 707).…”
Section: Populism and The Evolving Media Landscape: Needed Researchmentioning
confidence: 99%
“…However, several studies have indicated a positive relationship between an increase in media attention and the success of populist movements and their leaders (Boomgaarden and Vliegenthart 2007;Koopmans and Muis 2009;Bos, van der Brug, and de Vreese 2010;Roodjuin 2014), although there are also studies which challenge that argument. Bos and Brants (2014), for example, demonstrate that the populist styles, ideas and policies presented in the media might be far less prevalent than often claimed. Some studies stress that media coverage is essential for the public image of all political leaders, regardless of affiliation (Bos, van der Brug, and de Vreese 2011).…”
Section: Populist Party Life Cycle Modelmentioning
confidence: 99%